POPULISME AKAR KETAHANAN POLITIK IDENTITAS: REFLEKSI PASANG SURUT POLITIK ISLAM DARI ORDE LAMA HINGGA ORDE REFORMASI - Abdul Waid (Jurnal Dialog, 2016)
The force of Islam politics always goes through ebb and flow. Unfortunately, the Islam politics has never been a main force in political arena of Indonesia, whereas the most population of Indonesia is muslim. This article addresses the question what strategy should be implemented to make Islam politics survive longer and longer. As the result, the unity of Islam politics’ vision and mission is an urgent to do. To do this, Islam politics must have one figure that is able to unify the fragmented muslims in many parties by campaigning the populism politics movement to defend political identity (Islam) and is able to do reconciliation Islamic parties to garner more than 60% votes in election.